2019
DOI: 10.1364/ao.58.002174
|View full text |Cite
|
Sign up to set email alerts
|

Curved detectors for astronomical applications: characterization results on different samples

Abstract: Due to the increasing dimension, complexity and cost of the future astronomical surveys, new technologies enabling more compact and simpler systems are required. The development of curved detectors allows to enhance the performances of the optical system used (telescope or astronomical instrument), while keeping the system more compact. We describe here a set of five curved CMOS detectors developed within a collaboration between CEA-LETI and CNRS-LAM. These fully-functional detectors 20 Mpix (CMOSIS CMV20000) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…2 and 3. Although some recent developments [9,13,14] showed that such a detector is feasible in principle, we chose to impose a R = 500 mm cap. This middle ground allows to benefit from a partial correction of field curvature, while de-risking the production of 24 scientific grade curved CCDs.…”
Section: Curved Detector-based Spectrograph Designmentioning
confidence: 99%
“…2 and 3. Although some recent developments [9,13,14] showed that such a detector is feasible in principle, we chose to impose a R = 500 mm cap. This middle ground allows to benefit from a partial correction of field curvature, while de-risking the production of 24 scientific grade curved CCDs.…”
Section: Curved Detector-based Spectrograph Designmentioning
confidence: 99%
“…The impact of the curving process on these characteristics of the detectors has not been fully determined yet, while some manufacturer tested few prototypes and found increased values for the dark current (Gregory et al 2015), others found no clear performance degradation with respect to the flat sensor case (Lombardo et al 2019).…”
Section: Simulation Setup and Input Parametersmentioning
confidence: 99%
“…Use of such a detector allows us to exclude the field curvature correction measures from the optical design, increase the resolution, and achieve a lower distortion and higher image illumination, as well as decrease the overall system dimension. In particular, it was demonstrated that the use of curved detectors makes it possible to significantly increase the performance of astronomical instrumentation and receive images of previously unresolvable objects [9,10]. Similar advantages apply to the technology of freeform optics [11], which has emerged during the last decade and allows to create optical systems notable for their outstanding resolution, high aperture, large field of view, and compactness.…”
Section: Introductionmentioning
confidence: 95%